(untitled) (REMUNOM, 2024)
The management of stocker cattle and sequestration in confinement systems has proven to be an effective solution for producers seeking to increase productivity without expanding their production area. This technique optimizes the stocking rate management, allowing pastures to have rest periods, which promotes their recovery and conservation, especially during droughts. This prevents weight loss in animals, improving performance and ensuring stability in production. For producers with financial limitations, semi-confinement offers a more accessible alternative. In this system, animals remain on pasture but receive supplementation to compensate for nutrient deficiencies, accelerating weight gain and ensuring they reach ideal slaughter weight with higher carcass quality. This approach improves profitability and market competitiveness. Additionally, the integration of technologies, such as strategic supplementation and digital pasture monitoring, further enhances outcomes. These innovations optimize stocking rate management and reduce risks associated with climate and input costs. Thus, intensive management, combined with technology, results in higher productivity and sustainability, ensuring better economic returns and the preservation of natural resources.